PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KERJA MELALUI SEMANGAT KERJA PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DELI SERDANG - Murni Hati Giawa; Intan Murni Gulo; Elazhari (LPPM Universitas Cipta Mandiri, 2024)
To achieve loyalty, employees will usually first be satisfied with their job satisfaction within the company. If someone is at the desired level of job satisfaction, then their level of commitment to be loyal to the company will also increase. On the other hand, if someone who has low commitment to the company will appear to be withdrawing from the company, which will ultimately lead to the employee's decision to leave the company. Loyalty to the company, namely the extent to which an employee identifies with his workplace as shown by the desire to work, try his best and make a definite decision to leave the company if he does not make a fatal mistake. Based on the research results, the calculated t value for the service quality variable was 8.995 with a significant value of 0.000. This significant value is smaller than the significance limit value, which is 0.05. Apart from that, by looking at the positive coefficient value, the hypothesis which states that the service quality variable has a positive and significant effect on work loyalty is accepted. This means that if the quality of service increases, work loyalty will increase.